OUTSIDERS ON THE INSIDE: Mestizaje and the Economics of Colonial Desire in Sinibaldo de Mas and Francisco de Paula Entrala. - Tolliver, Joyce (Kritika Kultura, 2021)
Throughout the last twenty-five years of the Spanish colonization of the Philippines, Spaniards published essays and fiction that echoed the view that the colonial project was doomed to failure, clearly expressed in Sinibaldo de Mas's 1843 Informe secreto (Secret Report). Less attention is paid to nineteenth-century works by peninsulares that mirrored Mas's alternative plan preparing for Philippine "emancipation" and economically incentivizing mestizaje. Among these were the fiction and essays of the self-described "aplatanado" Francisco de Paula Entrala, which suggested that any failure of mestizaje as a normalizing colonial project was due to the shortcomings of the peninsular Spaniards themselves. In his 1881 Olvidos de Filipinas (Philippines Forgotten), Entrala's rhetorical shifts simultaneously grant him the authority of an insider to Manila culture and acknowledge his position as colonial outsider; while in his 1875 "El rostro y el alma" ("The Face and the Soul"), he plays with the conventions of romantic narrative and of costumbrismo to portray mestizaje as the economic salvation of the would-be colonizers and a "happy ending" to failed Spanish imperialism.